Philosophy of comics : an introduction - Cowling, Sam; Cray, Wesley (London [England] : Bloomsbury, 2022)
"What exactly is a comic? What is the difference between a comic and an illustrated novel? Could a comic be rightly counted as a work of literature? Thinking about comics raises a host of philosophical questions. Philosophy of Comics is an introduction to these questions and more. Exploring some of the peculiar features of comics, cartoons, and graphic novels, Sam Cowling and Wesley Cray chart a path through the field of the philosophy of comics. Using examples from a diverse range of comic genres and informed by case studies of classics such as Watchmen and The Flash , they tackle a variety of ethical, metaphysical, and aesthetic puzzles, including: - What does it takes to create-or destroy-a fictional character like Black Panther ? - Can all comics be adapted into films, or do some resist such treatment? - Is there really a genre of "superhero comics"? At a time of rapidly growing interest in graphic storytelling, this is an ideal introduction to the philosophy of comics and some of its most familiar and important questions"--
Case Study Questions -- Recommended Readings -- 9. What are The Limits of Comics? -- Obscenity and Pornography -- Pornography and Comics: A Brief History -- Fun Home vs. Duke Freshman: A Protest -- Identifying the Obscene -- Art vs. Pornography -- Conclusions -- Discussion Questions -- Case Study Questions -- Recommended Readings -- Glossary -- Index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Comic books, strips, etc. -- History and criticism; Philosophy: aesthetics,Comic book & cartoon art; Electronic books